2013
DOI: 10.1007/s10059-013-2269-x
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9 Promotes Invasion and Migration through p38 Mitogen-Activated Protein Kinase-Dependent NF-κB Activation in Gastric Cancer Cells

Abstract: S100A8 and S100A9 (S100A8/A9) are low-molecular weight members of the S100 family of calcium-binding proteins. Recent studies have reported S100A8/A9 promote tumorigenesis. We have previously reported that S100A8/A9 is mostly expressed in stromal cells and inflammatory cells between gastric tumor cells. However, the role of environmental S100A8/A9 in gastric cancer has not been defined. We observed in the present study the effect of S100A8/A9 on migration and invasion of gastric cancer cells. S100A8/ A9 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 37 publications
6
72
0
1
Order By: Relevance
“…In addition, MMP7 expression was somewhat reduced, indicating that endogenous S100A8 and S100A9 promoted the migration of CNE1 NPC cells; this is consistent with the conclusion that S100A8/A9 promotes colon tumor cell metastasis, as reported by Ichikawa et al (25). S100A8 and S100A9 may promote cell migration and invasion through p38 MAPK-dependent nuclear factor-κB activation (21). Further investigation is required to determine the molecular mechanisms underlying the promotion of CNE1 NPC cell migration by endogenous S100A8 and S100A9.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, MMP7 expression was somewhat reduced, indicating that endogenous S100A8 and S100A9 promoted the migration of CNE1 NPC cells; this is consistent with the conclusion that S100A8/A9 promotes colon tumor cell metastasis, as reported by Ichikawa et al (25). S100A8 and S100A9 may promote cell migration and invasion through p38 MAPK-dependent nuclear factor-κB activation (21). Further investigation is required to determine the molecular mechanisms underlying the promotion of CNE1 NPC cell migration by endogenous S100A8 and S100A9.…”
Section: Discussionsupporting
confidence: 90%
“…Further investigation is required to clarify the differential roles of S100A8 and S100A9 on MMP7 expression in CNE1 cells. Yong and Moon (17) demonstrated that expression level of MMP2 was decreased by 83% with S100A9 siRNA and by 52% with S100A8 siRNA, indicating that S100A8/A9 may increase MMP2 and MMP7, although this is inconsistent with the results reported by Kwon et al (21).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The present study implemented the Cox proportional hazards model, which demonstrated that protein S100-A8 is not an independent risk factor for prognosis in breast cancer. S100-A8 also assembles heterodimers with S100-A9, which increases matrix metalloproteinase (MMP)-2 or MMP-12 expression and activity to promote tumor cell migration and invasion (36,37). This suggests that the interaction of S100-A8 within heterodimers is able to affect its activity during the process of breast cancer progression.…”
Section: Cell Motility Locomotionmentioning
confidence: 99%
“…Recent studies have also shown that they play significant roles in cancer where they promote tumor growth and metastasis in a large number of cancers such as in breast, prostate and pancreatic cancer [232][233][234][235][236][237][238]. In tumors, recent studies have shown that S100A8/A9 regulates the accumulation of myeloid-derived suppres-sor cells (MDSC), and also promote the expansion of these cells, resulting in increased tumor growth [239][240][241][242][243].…”
Section: S100a8/a9mentioning
confidence: 99%